Optimization of Thermoelectric Generator (TEG) Configuration for Burning Sugarcane Bagasse as an Alternative Energy Source - Karim, Rahmiaty Abd.; Arbie, Asri; Yunus, Muhammad; Mursalin, Mursalin; Setiawan, Dewa Gede Eka; Ahmadi, Haerul (Journal of Science and Science Education, 2024)
Sugarcane bagasse is waste from the sugar industry which has the potential to be an efficient fuel for producing electricity by converting heat energy into electrical energy using a Thermoelectric Generator (TEG). TEG can be optimized to burn sugarcane bagasse as an alternative energy source in Indonesia. This research uses series and parallel configurations to test the optimal TEG configuration to increase energy conversion efficiency. The research results revealed that supercapacitors' parallel configuration produced the highest power in the 66th minute at 0.26 W. In comparison, the series configuration with supercapacitors produced 0.21 W of power in the 63rd minute. For the parallel configuration without supercapacitors, the energy produced reaches 0.20 W in the 69th minute, and the series configuration without supercapacitors produces 0.19 W in the 63rd minute. The parallel configuration shows more optimal performance than the series configuration, making it a promising solution in diversifying energy sources, especially in supporting efforts to utilize agricultural waste sustainably. Optimization of the thermoelectric generator configuration for burning sugarcane bagasse can be used as an alternative energy source.